Immunogenicity of vaccines for malaria-exposed populations - Bowyer, GSA (2018)
An efficacious malaria vaccine will be a necessary tool for malaria eradication, however current vaccine candidates have only demonstrated a moderate level of short-term efficacy. Additionally, these vaccines often display reduced immunogenicity and efficacy in the malaria-exposed target populations compared with the malaria-naïve populations in which they are initially tested. Reduced vaccine immunogenicity in malaria-exposed populations may affect vaccines for diseases other than malaria. The 2014-2016 Ebola outbreak in West Africa highlighted the need to produce effective vaccines against emerging infectious diseases. Many of the outbreak pathogens for which such vaccines are being developed have geographical distributions that overlap with areas of malaria transmission. Therefore being able to effectively vaccinate malaria-exposed individuals is a key requirement for this new generation of vaccines. This thesis aims to characterise the immunogenicity of candidate malaria and Ebola vaccines in detail and explores potential mechanisms of reduced immunogenicity in malaria-exposed populations. Experiments demonstrated that concomitant administration of viral vectored and VLP-based malaria vaccines caused a Th1-skewed cytokine response that was associated with reduced antibody titres and efficacy, similar to the immunosuppressive effect of acute malaria infection. Humoral, but not cellular, responses to malaria and Ebola vaccines were reduced in malaria-exposed adults and children but not in infants. Although this reduction was associated with malaria exposure in some cases, it was clear that other factors were involved. Further experiments revealed a role for cytomegalovirus infection in the reduction of vaccine immunogenicity in both malaria-naïve and malaria-exposed young adults. Overall this thesis highlights the importance of understanding what impacts immunogenicity in order to optimise vaccines for the target populations.